بنية الشخصية في رواية "لنرقص الترانتيلا ثم نموت" لعبد المنعم بن السايح - قادي, بدور; بن نونة, خديجة (جامعة الوادي - University of Eloued, 2023)
استطاع عبد المنعم بن السايح في روايته " لنرقص الترانتيلا ثم نموت" أن ينقلّ بدقة كبيرة وظائف الشخصيات وأن يقسّم أدوارها ويعطيها أبعاداً اجتماعية وسيكولوجية متوائمة مع الوضع الفلسطيني الراهن، واستطاع أيضا بكفاءة أن يوزع الأدوار على الشخصيات بمختلف أنماطها وأن يحركها على نسق متناغم بحيث تؤدي أدوارها دون أي إفراط أو تفريط، ولقد استطعنا التفطن إلى هذه النتائج بفضل المنهج البنيوي المدعم بالمنهج السيميائي . Summary: In his novel "Let's Dance the Tarantella and Then Die," Abd al-Mun'im bin al-Sayih was able to accurately convey the functions of the characters, divide their roles, and give them social and psychological dimensions that are compatible with the current Palestinian situation. He also efficiently distributed the roles among the characters with their diverse patterns and moved them in a harmonious manner, so that they perform their roles without any excess or deficiency. We were able to detect these results thanks to the structural approach supported by the semiotic approach.
Keywords: البنية، الشخصية، الرواية، عبد المنعم بن السايح; Structure, Character, Novel, Abd al-Mun'im bin al-Sayih.